Pea breeding - Moreno Mendoza, José Dilmer (North Carolina State University, 1987)
Pea crop, Pisum sativum,is one of the most important seed legumes, as such, the crop constitutes an important source of protein for human consumption. USA production is about 580,000 tons per year of green peas for processing by canning and freezing. Peas belongs to the family Papilionaceae, it is a self-pollinated crop (2n=14). Peas are planted in the field early in the spring after danger of frost has passed, and develop best under cool, moist conditions. The main objectives of the breeding program are: production of immature peas (maturity stage) increases of number of pods per node, as all the pods at a node mature more or less simultaneously; increase simultaneity of development of pods at successive nodes; increase content of protein and resistance to diseases and insects. Pisum germplasm is available from a number of sources (14 Institutions). Its center of origin is the Near East, Ethiopia and European Mediterranean. Most of the important characters are quantitatively inherited and polygenic control. Some of traits are controlled by single genes. Peas are subjected to many diseases. Interspecific hybridization is not success. Mutation have played an important role in its evolution. Breeding for most characters is based on hybridization, backcrossing and single selection.